The role of the public prosecutors in the repression of tax crimes - the Italian perspective - Carbone , Vincenzo (European Integration Studies, 2023)
The investigation and prosecution of tax crimes is characterized by the coexistence of administrative and criminal proceedings, which can lead to the imposition of multiple penalties. This paper therefore analyses the role of the public prosecutor’s office in the prevention and prosecution of tax crimes.